(untitled) (Medical Forum Monthly, 2024)
Fibrodysplasia ossaficans progressiva is an extremely rare and severely disabling, autosomal dominant condition that effects 1 in 2 million people. We report a 3 years old female child referred to radiology department from pediatric orthopedic clinic with complaints of multiple painful swellings over the back and inability to sleep due to discomfort. Radiological investigations that include - X-Rays and C.T Scan were done that revealed heterotopic ossifications in muscles, facia and in ligaments.X-Rays revealed bilateral hallus valgus deformity with microdactyly that is characteristic of fibrodysplasia ossificans progressive.